Early breakthrough of short‐chain perfluoroalkyl substances in adsorptive media treatment. Issue 3 (25th April 2022) - Crawford, Scott; Thomas, Ryan; Taylor, Fred; Dore, Sophia; Marley, Michael; Crawford, Laurel; Occhialini, Jim; McKnight, Taryn; Farmer, Norman
Abstract: Activated carbon (AC) adsorption continues to be the default technology to remove low levels of per‐ and polyfluoroalkyl substances (PFAS) from water, despite varying reports of the relatively early breakthrough of short‐chain PFAS and high operating costs. Ion‐exchange processes using regenerable and single‐use media have been emerging as practical alternatives which may provide improved treatment and system performance. However, long‐term performance with respect to the more difficult to remove short‐chain PFAS such as perfluorobutanoic acid and perfluorobutanesulfonic acid is less often reported. Treatability testing on PFAS‐impacted groundwater using batch‐equilibration reactors and column flushing apparatus experiments was implemented to compare removal efficiency, breakthrough, and longevity of various media, specifically for shorter chain PFAS. Adsorbents tested included surface‐modified natural media, synthetic resin, and AC. Results indicated that both surface modified natural media and AC achieved >99 percent removal of all detected PFAS after approximately 10, 300‐bed volumes (16 weeks) of column flushing, and outperformed the selected resin under site‐specific conditions. In addition, unconventional breakthrough patterns (i.e., the breakthrough of longer chain PFAS before shorter chain PFAS) were observed for some PFAS including perfluoropentanoic acid, perfluorohexanesulfonic acid, and perfluorooctanesulfonic acid. The results of this study suggested that, while the generally accepted breakthrough patterns for PFAS can be reasonably anticipated, column flushing studies were preferred over batch sorption tests to reveal site‐specific or media‐specific breakthrough patterns that can impact overall performance.